2007
DOI: 10.1677/jme.1.02196
|View full text |Cite
|
Sign up to set email alerts
|

Bone morphogenetic protein 2 and activin A synergistically stimulate follicle-stimulating hormone β subunit transcription

Abstract: Transforming growth factor b superfamily ligands regulate pituitary FSH production and secretion. The best-described examples are the activins and inhibins, which respectively stimulate and hinder Fshb subunit transcription in gonadotrope cells. More recently, members of the bone morphogenetic protein (BMP) sub-family were shown to regulate FSH production in a manner analogous to the activins. Here, we used the murine gonadotrope cell line, LbT2, to investigate mechanisms through which BMP2 regulates the Fshb … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 71 publications
2
54
0
Order By: Relevance
“…These proteins can affect embryonic development and the formation of bones and organs, playing a critical role in the early mammalian development and nervous system differentiation. Recent data showed that bone morphogenetic proteins stimulate FSHβ transcription (Lee et al, 2007;Ho and Bernard, 2009). PTGFRN can inhibit prostaglandin F2α by interacting with its receptor.…”
Section: Discussionmentioning
confidence: 99%
“…These proteins can affect embryonic development and the formation of bones and organs, playing a critical role in the early mammalian development and nervous system differentiation. Recent data showed that bone morphogenetic proteins stimulate FSHβ transcription (Lee et al, 2007;Ho and Bernard, 2009). PTGFRN can inhibit prostaglandin F2α by interacting with its receptor.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore examined the potential for GDF9 to display either 1) autocrine actions on FSH synthesis and secretion by gonadotrophs in the manner of activin that is subject to antagonism by inhibin (Corrigan et al 1991, Li et al 1998 or 2) synergism with activin to stimulate FSH production in the manner of BMP (Lee et al 2007b, Nicol et al 2008. However, GDF9 (1-50 ng/ml) did not significantly increase FSH secretion (Fig.…”
Section: Lack Of Gdf9 Effects On Fsh Secretion By Rat and Mouse Gonadmentioning
confidence: 99%
“…The effect on basal activity suggested that endogenous signaling via one or more of these receptors might contribute to the high 'basal'Hsd17b1 expression and 17b-HSD1 enzymatic activity in these cells. We previously showed that the Inhbb, but not Inhba subunit is expressed in LbT2 cells (Lee et al 2007). Homodimers of the INHBB protein form activin B. Activin B was implicated as the physiologically relevant activin in gonadotropes in vivo (Roberts et al 1989, Corrigan et al 1991, DePaolo et al 1992.…”
Section: Resultsmentioning
confidence: 99%